1998
DOI: 10.2337/diacare.21.11.1870
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of risk for severe hypoglycemia among adults with IDDM: validation of the low blood glucose index.

Abstract: LBGI provides an accurate assessment of risk of SH. In the traditional relationship history of SH-to-future SH, LBGI may be the missing link that reflects present risk. Because it is based on SMBG records automatically stored by many reflectance meters, the LBGI is an effective and clinically useful on-line indicator for SH risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
228
3
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 280 publications
(236 citation statements)
references
References 0 publications
3
228
3
1
Order By: Relevance
“…The 90 th percentile HYPO score and LBGI was 377 and 3.97, respectively, lower than the values found in a previous study for high risk of severe hypoglycemia (LBGI of 5; 78 th percentile according to Kovatchev et al) [15]. The HYPO score was correlated with the LBGI (Table 2) and the HYPO score of recalled episodes over the previous year showed a weak correlation with the HYPO score measured over the fourweek SMBG period (r = 0.28, P < 0.05).…”
Section: Discussioncontrasting
confidence: 48%
See 3 more Smart Citations
“…The 90 th percentile HYPO score and LBGI was 377 and 3.97, respectively, lower than the values found in a previous study for high risk of severe hypoglycemia (LBGI of 5; 78 th percentile according to Kovatchev et al) [15]. The HYPO score was correlated with the LBGI (Table 2) and the HYPO score of recalled episodes over the previous year showed a weak correlation with the HYPO score measured over the fourweek SMBG period (r = 0.28, P < 0.05).…”
Section: Discussioncontrasting
confidence: 48%
“…However, in our study group, the 90 th percentile value of the HYPO score was 376.9. In addition, the value of LBGI was lower that the cutoff value for a high risk of hypoglycemia suggested by Kovatchev et al (LBGI > 5) [15]. These differences can be explained by the fact that the duration of diabetes in our group was different from that in Ryan et al We observed that the hypoglycemic index weakly correlated with the duration of diabetes, as was the case in previous studies [15,24].…”
Section: Declaration Of Competing Interestscontrasting
confidence: 48%
See 2 more Smart Citations
“…Youths' ADRR scores were calculated using the original formula 8 and analyzed as continuous and categorical variables based on published adult risk categories: low risk, ADRR < 20; moderate risk, ADRR 20-40; and high risk, ADRR > 40. The LBGI and HBGI were also developed by Kovatchev et al 8,12 and use normalized transformations of SMBG values, similar to the ADRR. However, LBGI and HBGI were designed to generate scores that have a near-zero correlation with each other, making them more highly predictive of episodes of hypo-and hyperglycemia, respectively.…”
Section: Methodsmentioning
confidence: 99%